Free Curriculum and Policy of Islamic Religious Education Learning: Substance of Self-directed Learning and Continuous Understanding of Religion - Musiarifsyah Putra; Habiburrahim; Silahuddin (Wasatha: Jurnal Studi Islam dan Humaniora, 2024)
Kurikulum Merdeka, a concept introduced in the Indonesian educational system, aims to enhance the autonomy of educational institutions in tailoring curricula to local needs and students' development. This approach emphasizes active student participation, collaboration, and the relevance of learning materials, particularly within the realm of Islamic Religious Education (PAI). By integrating various strategies such as active learning methods and technology, Kurikulum Merdeka facilitates the seamless incorporation of PAI into the curriculum, fostering a deeper understanding and continuous practice of Islamic teachings. Furthermore, initiatives like problem-based projects and relevant extracurricular activities contribute significantly to strengthening comprehension and practical application of religious values. Consequently, Kurikulum Merdeka not only fosters independent learning and sustains religious understanding but also lays a solid foundation for character formation and moral development among students, thereby reinforcing the relevance of Islamic teachings in modern life.